A Case With IgG4-Related Spinal Pachymeningitis Causing Spinal Cord Compression - Zhang, Rensheng; Gao, Jiguo; Zhao, Teng; Zhang, Beilin; Wang, Chenglin; Wang, Chao; Cui, Lexiang; Chen, Jiafeng; Fang, Shaokuan (Frontiers in Neurology, 2020)
Immunoglobulin G4 (IgG4)-related disease is a systemic disease characterized by sclerosing lesions and an increased serum IgG4 level. This condition can involve any organ, but IgG4-related spinal pachymeningitis is relatively rare.In the current study, we report a case of spinal cord compression caused by IgG4-related spinal pachymeningitis.A 39-year-old man presented to us with a 15-day history of back pain and a 3-day history of dysuresia, exacerbated by weakness in the lower extremities for 2 days. Cervical magnetic resonance imaging (MRI) showed strip-shaped abnormal signals along the anterior and posterior borders of the spinal cord at the C5–T4 levels. The IgG level in cerebrospinal fluid was 718.0 mg/L. Thoracic MRI revealed strip-shaped abnormal signals with remarkable enhancement along the anterior and posterior borders of the dural sac at the T1–T6 levels. Histopathological examination confirmed IgG4-related spinal pachymeningitis. The symptoms worsened rapidly, and surgical resection of the space-occupying lesion in the vertebral canal was performed for spinal decompression. Corticosteroid therapy was administrated, and the patient’s motor functions were mildly improved.IgG4-related disease can manifest as spinal pachymeningitis and cause spinal cord compression. Clinicians should be aware of this rare condition, and early diagnosis, timely surgical decompression, and appropriate corticosteroid therapy should be highlighted.